Study the Temperature Dependence of EXAFS Cumulants of Si and Ge by the Anharmonic Correlated Einstein Model - Hung, Vu Van; Hieu, Ho Khac (Communications in Physics, 2011)
In present article, the anharmonic correlated Einstein model has been used to study the temperature dependence of Extended X-ray absorption fine structure (EXAFS) cumulants of silicon and germanium crystals. The analytical expressions of the first, second and third cumulants of silion and germanium have been derived. Our numerical calculations are compared with the experimental values and also with other theoretical results showing the good agreement.